The Nature and Extent of Component Analyses for Improving or Mitigating Behavior: A Systematic Review. Issue 1 (January 2022) - Riden, Benjamin S.; Markelz, Andrew M.; Ruiz, Salvador; Kent, Sarah; Pavelka, Shelby K.; Chitiyo, Argnue
A component analysis is an approach where two or more independent variables are evaluated as a package and independently. The approach is used to assess and identify which component of a treatment package is the most effective. The purpose of this review is to document the application of component analyses to improve or mitigate non-academic behaviors with individuals with disabilities. We identified 21 research articles that used a component analysis to evaluate treatment packages with students who were identified as having or at-risk for a disability in classroom and/or alternative settings. Results from reviewing 21 articles (22 cases) indicate that 11 intervention packages had a single component that was critical for successful behavior change. Two articles suggested the entire intervention package was necessary while nine articles did not report a critical component or had variable results pertaining to critical components. The benefits and drawbacks of using component analyses for single case research are discussed. Implications for future research are also presented.